Optimization of Dye Removal from Textile Wastewater using Activated Carbon from Sawdust - O. A. A. Eletta (Nigerian Journal of Technological Development, 2018)
This study is aimed at developing an adsorbent from sawdust for optimum removal of dye from textile wastewater.  The adsorbent was developed, characterised and, the adsorptive capability for the removal of dye was determined by optimizing the process parameters (adsorbent dosage, contact time and agitation speed) using Response Surface Methodology. The physical and chemical characterization of the effluent was carried out before and after the adsorption studies. From the results, a maximum adsorption capacity of 98.5 % was obtained at the optimized conditions of 1.5 g, 90 min and 275 rpm for adsorbent dose, contact time and agitation speed respectively. The ANOVA of the regression model showed that the model is highly significant with R2 of 0.98. Further analysis carried out revealed that, in addition to dye removal, trace metals were also adsorbed in the process. This fact was established when the concentration of copper in the wastewater was found to decrease from 0.09 ppm to 0.03 ppm corresponding to 66.7 % removal at the end of the process.